2012
DOI: 10.5402/2012/560376
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Prevalence in a Suburban School of Famaillá, Tucumán, Argentina

Abstract: Prevalence of intestinal parasites was investigated in rural primary school children in Famaillá city, Tucumán province, Argentina. Stool specimens from 149 school children were collected. The prevalence rate of intestinal parasite infections was 86.6%. No significant differences were observed in the distribution by age or by sex. Blastocystis hominis was the most commonly found protozoan parasite (54.4%), followed by Entamoeba coli (35.6%), Giardia lamblia (24.8%), and others (16.7%). Enterobius vermicularis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
5
0
5
Order By: Relevance
“…In this regard, studies in Venezuela and Paraguay reported a lower prevalence (63% and 35%, respectively) (19,20), but similar or slightly higher prevalence in studies performed in other Latin American countries. (21,22) In Argentina, prevalence was not uniform either since the distribution of parasitic infections changed according to region: values were over 80% in the north (16,23), between 60% and 70% in the center (24,25), and lower than 40% in the south (8).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies in Venezuela and Paraguay reported a lower prevalence (63% and 35%, respectively) (19,20), but similar or slightly higher prevalence in studies performed in other Latin American countries. (21,22) In Argentina, prevalence was not uniform either since the distribution of parasitic infections changed according to region: values were over 80% in the north (16,23), between 60% and 70% in the center (24,25), and lower than 40% in the south (8).…”
Section: Discussionmentioning
confidence: 99%
“…La mayor frecuencia de parasitosis en Misiones (nordeste) contrasta con la encontrada en Chubut (sur), lo que coincide en parte con lo informado para otras localidades del norte (Corrientes, Salta y Tucumán) (14, 28, 29) y el sur del país (Neuquén) (30). Evidentemente, las condiciones climáticas y los suelos de Misiones favorecen la presencia y la transmisión de enteroparásitos, algo que el clima frío y seco y los suelos pobres en materia orgánica de Chubut no favorecen.…”
Section: Discussionunclassified
“…Several cross-sectional studies carried out in the school-aged children have reported the incidence of IPD to be 22.9% in China (14), 28.8% in Iran (15), 86.6% in Argentina, 55.8% in Chile and 77.8% in Peru (16), and the IPD to be endemic in mountainous and rural regions of Cuba (17). The prevalence of IPD has been reported to vary from 9.6% to 60.4% in different regions of our country (5,6,9).…”
Section: Discussionmentioning
confidence: 99%